Synthesis and Biological Evaluation of Cystobactamid 507: A Bacterial Topoisomerase Inhibitor from Cystobacter sp. - Moreno, María; Elgaher, Walid A. M.; Herrmann, Jennifer; Schläger, Nadin; Hamed, Mostafa M.; Baumann, Sascha; Müller, Rolf; Hartmann, Rolf W.; Kirschning, Andreas (Synlett, 2015)
The first total synthesis of cystobactamid 507, a member of a class of new natural products with strong inhibitory activity towards bacterial topoisomerases, is reported. Synthetic key challenges are the central tetrasubstitued arene and the low chemical reactivity of anilines and ortho-phenolic and isopropoxy-substituted benzoic acids. Biological evaluations demonstrate that cystobactamid 507 inhibits several Gram-positive pathogens but at significantly lower concentrations than described for the larger members of this natural product family.
Keywords: amides; antibiotics; medicinal chemistry; natural products; total synthesis